Toward the Classical Description of Halogen Bonds: A Quantum Based Generalized Empirical Potential for Fluorine, Chlorine, and Bromine - Santos, Lucas A; da Cunha, Elaine F F; Ramalho, Teodorico C (The journal of physical chemistry. A, 2017)
The electronic effects in supramolecular systems are a great challenge for computational chemistry, and the understanding of ligand-protein interactions driven by halogen bonds can be limited by molecular mechanics point of view. In fact, the variations of the halogen bond acceptors, such as an aromatic ring and electrons lone pairs, restrict the classical approximations even more. Our work enhances the statement that halogen bonds are led mainly by orbital interactions via σ*C-X. Nonetheless, we have pointed a straight relationship between the maximum ESP value on the σ-hole and the LUMO energy levels of the halogen bond donor. In line with this scenario, the current work introduces a new promising empirical potential based on quantum parametrizations able to describe general halogen bonded systems. The new parameters allow force fields to detect variations on the molecular electronic structure of halogenated organic compounds to improve the description of fluorine, chlorine, and bromine in halogen bonds.